Safety and efficacy of naproxen for fever and acute pain in preschool children: a systematic review. (December 2022) - Mathiesen, Sidsel; Jørgensen, Adam E.M.
Abstract : Summary: Preschool children may require acute pain and fever management beyond the effects of paracetamol. Ibuprofen, an NSAID, is the first-choice analgesic add-on in children, as its effects and safety profile are well-known in children. In some countries, however, ibuprofen in oral solution is not available; thus, naproxen (another NSAID) could be an alternative. In this systematic review, we evaluated the effect of naproxen on fever and acute pain as well as related adverse events in preschool children. Although the evidence was limited, naproxen appears to be well tolerated and efficient in treating acute pain and fever in preschool children.